Pengurusan penglibatan pelajar dalam amali sains - Nurzatulshima Kamarudin,; Lilia Halim,; Kamisah Osman,; T Subahan Mohd. Meerah, (penerbit ukm, 2009)
Practical method in science subject is an instructional method that gives students the opportunity to do their own scientific investigation through planning, performing and discussing. The purpose of this study was to explore the way teachers manage their students, in order to increase their involvements in science practical work. This qualitative case study studied three experienced science teachers by garnering data through teachers’ observation, students’ interview and analysis of students’ documents. All data were analyzed manually. This study found that students’ involvement in Additionally, it was also found that patrolling and checking the students’ progress during practical session, giving out positive rewards and cooperation from lab assistant in monitoring students, did help in increasing students’ involvement during practical work. Certainly, active students’ involvement throughout the teaching and learning process will help in producing human capital equipped with criteria such as creative, critical and innovative. science practical are high when the teacher manage the students by dividing them into a group of three to five, and by disseminating the work.